P163 A multicentre retrospective cohort comparison of aetiology and survival in patients with chronic hypersensitivity pneumonitis versus idiopathic pulmonary fibrosis. (December 2018) - Barratt, SL; Adamali, HI; Creamer, A; Duckworth, A; Fallon, J; Gibbons, MA; Gooptu, B; Nancarrow, T; Pepperell, J; Spiers, AS; Stone, RA; Wollerton, RL; et al.
Abstract : Introduction: Hypersensitivity pneumonitis is a complex syndrome believed to result from repeated inhalation and sensitisation to a variety of antigenic stimuli. The majority of cases are classified as chronic and may result in fibrotic progression which can be hard to distinguish from idiopathic pulmonary fibrosis (IPF). Precise aetiology and optimal management strategies are less well defined than for IPF, although clinical trials exploring efficacy of pirfenidone (NCT02496182 ) and nintedanib (NCT02999178 ) are in progress. Objectives: To establish a large, UK-based, multicentre, retrospective cohort of patients with cHP to facilitate detailed investigation of patient demographics, management and prognosis. Methods: Multicentre evaluation of clinical data for patients presenting to the interstitial lung disease clinics at the North Bristol NHS Trust, University Hospitals of Leicester NHS Trust, Taunton and Somerset NHS Foundation Trust and the Royal Devon & Exeter NHS Foundation Trust between 2005 and 2018. Basic demographics and survival were compared using chi-square test with Yates correction (gender), Mann-Whitney U-test (age at presentation) and Kaplan-Meier Survival analysis in Graphpad Prism. Results: In total, 397 patients with a diagnosis of cHP were identified, compared with 1068 patients with IPF. There was a significant difference in age at diagnosis between cHP and IPF (median 72.0 vs 75.6, p<0.0001), and a highly significant difference in gender distribution, with a greater proportion of women presenting with cHP than men (237 female vs 160 male, p<0.001), in stark contrast to IPF (246 female vs 822 male). cHP was associated with a better prognosis than IPF (p<0.05), with a median survival of 7.1 years following diagnosis compared with 3.0 years for IPF. Conclusions: Despite challenges in diagnosing cHP (as demonstrated by Walsh et al 1 in their review of UK MDT agreement where HP has only a fair kappa score of 0.29) and in line with published literature, our cHP cohort has a female preponderance and is associated with better survival than IPF. This cohort will provide a crucial resource for more detailed analysis of patient data (e.g. spirometry and response to therapy). Reference: Walsh SL, et al. Lancet Respir Med 2016;4:557–65.